2011
DOI: 10.1111/j.1365-2362.2011.02559.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, SHBG and risk of type 2 diabetes in the second evaluation of the Pizarra cohort study

Abstract: Low levels of testosterone and SHBG increase the risk of T2D in men, and high levels of testosterone increase the risk of insulin resistance in women. The association between TT levels and the risk of T2D is not completely independent of other variables, such as exposure time, adiposity, insulin resistance or SHBG levels. This study also shows that the different responses between men and women are probably because of the protective effect of SHBG, levels of which are higher in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 28 publications
1
43
0
1
Order By: Relevance
“…Five studies found an association between lower total T and incident diabetes [49, 55, 47, 58, 57], while 3 studies reported no association [46, 59, 48]. Two studies found an association between lower bioavailable or free T and incident diabetes [49, 57], while 3 studies reported no association [51, 46, 59]. One study examined total E2 and found an association [48], while another examined total and bioavailable E2 in men and diabetes and found no association [55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies found an association between lower total T and incident diabetes [49, 55, 47, 58, 57], while 3 studies reported no association [46, 59, 48]. Two studies found an association between lower bioavailable or free T and incident diabetes [49, 57], while 3 studies reported no association [51, 46, 59]. One study examined total E2 and found an association [48], while another examined total and bioavailable E2 in men and diabetes and found no association [55].…”
Section: Resultsmentioning
confidence: 99%
“…One study examined total E2 and found an association [48], while another examined total and bioavailable E2 in men and diabetes and found no association [55]. Five studies examining SHBG found an association between lower SHBG and incident diabetes [49, 51, 46, 58, 57]; 4 did not [53, 56, 59, 48], particularly after adjustment for waist measures. Tibblin et al [57] examined IGT as well as diabetes as an outcome and also reported that lower total T was associated with incident IGT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma samples used in this study were from 315 men from the cohort of the Pizarra Study in which 1134 people (443 men and 691 women) selected randomly from the municipal census of Pizarra (a southern Spanish population) were included. After 6 years, 928 (341 men and 587 women) were evaluated again [62]. SHBG serum levels were significantly higher in subjects using olive oil for cooking compared with subjects using sunflower oil.…”
Section: Shbg Upregulation By Oleatementioning
confidence: 99%
“…6,7,8 Further, reduced total testosterone (TT) levels have been associated with insulin resistance and subsequent risk for developing T2DM. 9,10 Total testosterone includes both unbound and proteinbound testosterone and is measured by radioimmunoassays or immunometric assays. A single random sample provides a good approximation of the average testosterone concentration with the realization that testosterone levels fluctuate in response to pulsatile LH.…”
Section: Introductionmentioning
confidence: 99%